Thermomagnetic properties of very heavy fermions suitable for adiabatic demagnetisation refrigeration at low temperature - Sereni, Julian Gustavo Renzo (2020)
With the aim to improve the performance of classical paramagnetic salts for adiabatic refrigeration processes at the sub-Kelvin range, relevant thermodynamic parameters of some new Yb-based intermetallic compounds are analyzed and compared. Two main applications are considered: i) those requiring temperature fixedpoints to be reached applying magnetic fields of moderate intensity for satelliteapplications, and ii) those which can be used for controlled thermal drifts in laboratory applications. Different thermomagnetic trajectories of the entropy are identifieddepending on respective specific heat behaviors and the constraints imposed by theNernst postulate at the sub-Kelvin range. Some simple relationships are proposed tocompare the diverse magnetocaloric characteristics of different systems. This procedure allows to include the classical Cerium-Magnesium-Nitride (CMN) salt in thatcomparison.